Moderating Role of Leverage and Profitability in the Relationship Between Eco-Efficiency and Firm Value in Consumer Goods Sector - Bernadeta Dian Saputri; Umu Khouroh; Irany Widhiyastiti; Lilik Kustiani (University of Merdeka Malang, 2025)
This research aims to examine the influence of company value on eco-efficiency with leverage and profitability as moderating variables. Companies that have implemented environmentally friendly concepts in their operational activities are expected to have higher share prices which will lead to an increase in company value. Eco-efficiency is implemented with ISO 14001 certification. Leverage is measured using Debt Equity Ratio (DER) and Profitability is measured using Return On Assets (ROA). This research also uses Earning Per Share (EPS) and Book Value (BV) as control variables. This research uses a sample of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange. The sample extraction technique used was purposive sampling with the criteria of companies presenting financial reports for the 2017-2021 period, resulting in 26 companies being obtained. This research is research that uses secondary data in the form of financial reports. This research uses the Moderated Regression Analysis (MRA) method. The research results show that when eco-efficiency is tested for its influence together with other variables, the results do not affect company value, but if eco-efficiency is tested alone, the results are significantly positive for company value. Based on the MRA test results, leverage and profitability as moderators are both unable to moderate the relationship between eco-efficiency and firm value.